Genome-wide characterization and expression profiling of the HD-ZIP gene family in Acoraceae under salinity and cold stress - Zhang, Diyang; Zhao, Xuewei; Huang, Ye; Zhang, Meng-Meng; He, Xin; Yin, Weilun; Lan, Siren; Liu, Zhong-Jian; Ma, Liang (Frontiers in Plant Science, 2024)
The Homeodomain-Leucine Zipper (HD-ZIP) transcription factors play a pivotal role in governing various aspects of plant growth, development, and responses to abiotic stress. Despite the wellestablished importance of HD-ZIPs in many plants, their functions in Acoraceae, the basal lineage of monocots, remain largely unexplored. Using recently published whole-genome data, we identified 137 putative HD-ZIPs in two Acoraceae species, Acorus gramineus and Acorus calamus. These HD-ZIP genes were further classified into four subfamilies (I, II, III, IV) based on phylogenetic and conserved motif analyses, showcasing notable variations in exon-intron patterns among different subfamilies. Two microRNAs, miR165/166, were found to specifically target HD-ZIP III genes with highly conserved binding sites. Most cis-acting elements identified in the promoter regions of Acoraceae HD-ZIPs are involved in modulating light and phytohormone responsiveness. Furthermore, our study revealed an independent duplication event in Ac. calamus and a one-to-multiple correspondence between HD-ZIP genes of Ac. calamus and Ac. gramineus.Expression profiles obtained from qRT-PCR demonstrated that HD-ZIP I genes are strongly induced by salinity stress, while HD-ZIP II members have contrasting stress responses in two species. HD-ZIP III and IV genes show greater sensitivity in stress-bearing roots. Taken together, these findings contribute valuable insights into the roles of HD-ZIP genes in stress adaptation and plant resilience in basal monocots, illuminating their multifaceted roles in plant growth, development, and response to abiotic stress.